Inorganic phosphorus level in the blood serum de lactating cows in the "Zona da Mata region" of Minas Gerais State – Brazil - Dayrell, Milton de Souza; Deresz, Fermino (Pesquisa Agropecuaria Brasileira, 2014)
During one year (Year I) blood samples were taken from lactating cows on farms of Piau, Rio Novo and Rio Preto counties, MG, Brazil, where mineral supplementation was not practised. During the same period, blood samples were taken from cows at the Centro Nacional de Pesquisa de Gado de Leite (CNPGL), of EMBRAPA, in Coronel Pacheco, MG, Brazil, where the animals were supplemented with phosphorus. During another year (Year II), the cows of Piau and Rio Novo counties received mineral supplementation with and without phosphorus, respectively, and in both cases blood sample were taken bimonthly for inorganic phosphorus (Pi) analysis. Samples of molasses grass (Melinis minutiflora) were taken from the pastures, for phosphorus analysis. In Year I, the annual average serum level of Pi (mg/100 ml) were, respectively, 4.45 ± 0.75, 5.23 ± 0.81, 4.77 ± 0.83 and 5.63 ± 0.81, for cows from Piau, Rio Novo, Rio Preto and CNPGL. The supplementation with phosphorus during the Year II had a significant effect (P<0.05) on the serum level of this element in the cows from Piau. Based on the general state of the herds in Piau and Rio Preto counties, with low levels of phosphorus in the pastures and in the blood, together with the generally low milk production, phosphorus supplementation was recommended in these areas.